Analisis Morfometri dan Morfostruktur Lereng Kejadian Longsor di Kecamatan Banjarmangu Kabupaten Banjarnegara - Kuswaji Dwi Priyono; P Priyono (Universitas Muhammadiyah Surakarta, 2008)
The aims of this research are: (a) to study and classify the landslide hazard level, and (b) to analysis morphometry and morphostructure slope at occurrence slides in the research area. The sampling method applied in this research was stratified sampling, landform units were applied as strata. The sample within strata was determined according the landslide hazard based factor that caused landslides. Analysed of morphometry and morphostructure conducted in described of landform units. The landslide location was mapped by determining landslide point with Global Position System (GPS), and morphometry slope analysis in three images with Digital Elevation Model (DEM) analysis. The results showed that the degree of landslide hazard in the research area could be classified into 9 units landform with 5 landslide hazard level, from very low until very high. At very high landslide hazard existed occurrence landslides at most, whereas at very low landslide hazard existed occurrence at least. From slope morphometry aspect, the point of the most landslide case is in mountain midle slope (11), lower slope (9), and upper slope (5). Flows type, soil fall, and rockfall all happen in lower slope. Landslide types almost (80%) happen in lower slope, whereas slump type happen in upper, middle, and lower slope. From slope form aspect, 70% landslide cases happen in concave slope position and slope classes 3-5 (9%). From morphostructure aspect, the research area hasn’t difference because of weathering level and litology structure condition which is relatively similar. Concave and aslant slope condition become the concentration point of surface flow water and under surface which are predicted be the most influence factor that cause landslide.